Effect of tapering's announcement by the Fed on North African countries and MENA and their integration in the international financial system - (:unkn) unknown (My University, 2019)
The first purpose of this thesis is to assess the impact of tapering’s announcement by the Fed during the period 2013 / 2015, and the impact these announcements had on assets prices in North Africa and more generally in MENA and African countries with the most developped financial sectors. We will assess, by studying the relevant events, the vulnerability of those countries to the shock in the international monetary policy sequence; consequently enabling a characterization of its impact, even on countries with relatively lowly developped financial markets. The second purpose of this thesis is to investigate the position of these countries within a large sample of MENA economies, and the remainder of the international financial system using a topological network. This enables to outline the interactions that bind those countries with each other, and also with the rest of the network —financial markets of advanced economies and other emerging economies. This thesis tackles a scarcely covered theme within the existing literature for the selected countries and also sheds new light on the question of financial integration using an atypical methodology.
Keywords: African Research